EFFECT OF GOODWILL ON THE PERFORMANCE OF THE ORGANIZATION OF THE CONSTRUCTION SECTOR - Okrepilov, Vladimir; Gravit, Marina; Nedviga, Ekaterina; Oleg, Dudnik (Journal of Applied Engineering Science, 2016)
There are issues of Goodwill and reputation risk. Particular attention is paid to the development of national standards for the evaluation of the experience and reputation of organizations. It is described the justification of creating the standard for evaluation of the experience and reputation of the building organizations. There is the method of valuation of goodwill, intangible assets that evaluates construction company. The methodology includes five factors, each of which includes some subfactors. The assessment according to this method of Russian standard 56002-2014 "Evaluation of experience and reputation building organizations" the construction company will be assigned a code of business reputation.